Method for treating zinc-containing dust and co-producing alkaline pellets

Through calcification roasting and ammonia leaching treatment technology, zinc-containing dust is converted into recyclable resources, and the preheating roasting temperature of alkaline pellets is reduced, which solves the low efficiency of zinc-containing dust treatment and the energy consumption of alkaline pellet production in steel enterprises. The high problem has achieved the goal of efficient recycling and energy conservation and consumption reduction.

CN119194062APending Publication Date: 2024-12-27CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411342271.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Steel enterprises are facing the problems of low zinc-containing dust treatment efficiency and high energy consumption for alkaline pellet production, making it difficult to achieve efficient recycling and energy conservation and consumption reduction.

Method used

By mixing zinc-containing dust with calcifier in proportion, adding binder and water for blocking treatment, calcification and roasting are carried out to convert zinc ferrate into zinc oxide, and zinc is recovered through ammonia leaching, and then with iron concentrate powder, etc. Materials prepare alkaline pellets to reduce the preheating and roasting temperature to improve production efficiency.

Benefits of technology

It realizes efficient recycling and utilization of zinc-containing dust and efficient preparation of alkaline pellets, reduces carbon emissions and energy consumption, improves the compressive strength of pellets, and is suitable for energy-saving and consumption-reducing targets for steel production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194062A_ABST
    Figure CN119194062A_ABST
Patent Text Reader

Abstract

The invention discloses a method for treating zinc-containing dust and co-producing alkaline pellets, which comprises the following steps of: (1) fully and uniformly mixing the zinc-containing dust and a calcification agent in proportion and then adding a binder and water to carry out agglomeration treatment, (2) carrying out calcification roasting on mixed material agglomerates obtained after agglomeration, (3) crushing and levigating the agglomerates obtained after roasting in the step (2) and then carrying out ammonia leaching treatment, and (4) the leaching residues dried in the step (3) are fully and evenly mixed with iron ore concentrate powder, a binding agent and water to prepare alkaline green pellets, and the green pellets are dried, preheated, roasted and cooled to obtain the alkaline pellets. According to the method, the zinc-containing dust of the steel plant can be absorbed in the plant, meanwhile, the preheating roasting temperature of the alkaline pellets is reduced, the time is shortened, efficient production of the alkaline pellets is guaranteed, and the method has an important promoting effect on achieving the purposes of energy conservation and consumption reduction in steel production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of iron and steel metallurgy and ore dressing and separation, and relates to a method for treating zinc-containing dust and co-producing alkaline pellets. Background Art

[0003] At present, the traditional treatment methods for zinc-containing dust in the steel industry are divided into three types: pyrometallurgy, hydrometallurgy and pyrometallurgy-wet combination. When the wet method is used to treat zinc-containing dust in steel plants, the zinc leaching rate and production efficiency are generally low, the leached slag is difficult to recycle as raw materials for steel plants, and it cannot meet the stacking requirements of environmental protection laws. The pyrometallurgical process has high production efficiency and large processing scale for the treatment of zinc-containing dust, but the pyrometallurgical process cannot achieve the extraction of non-ferrous zinc elements. The pyrometallurgical-wet combination is an important trend in the development of resource utilization technology for zinc-containing dust in steel plants. First, secondary zinc oxide rich in various elements and sponge iron with a certain grade are obtained through pyrometallurgy, and then various valuable elements are extracted from the secondary zinc oxide through wet method. With the improvement of environmental protection requirements, how to achieve the internal consumption of zinc-containing dust in steel plants and achieve efficient recycling has become a major challenge facing steel companies.

[0004] In addition, the current blast furnace ironmaking is mainly based on a charge structure of high-basicity sintered ore with acidic pellets and a small amount of lump ore, and the proportion of pellets is mostly within 20%. This charge structure can increase blast furnace production and save coke to a certain extent, and improve economic benefits. However, in terms of pollution and energy consumption, the pollution load ratio of the sintering process is 5 times that of the pelletizing process, among which sulfur dioxide emissions are twice that of pelletizing; energy consumption is twice that of pelletizing. Using pellets with a grade 5% higher than that of sintered ore can reduce the fuel ratio by more than 13%.

[0005] A large number of production practices have proved that increasing the proportion of pellets fed into the furnace can significantly reduce the amount of slag and fuel consumption while improving the utilization coefficient of the blast furnace. However, simply increasing the proportion of ordinary acidic pellets fed into the furnace cannot meet the needs of the slag-making system in the blast furnace ironmaking process. In order to stabilize the blast furnace slag type and increase the basicity of the pellets, it is necessary to replace the high-basicity sintered ore with alkaline pellets to build a new charge structure based on pellets. Therefore, building a new charge structure based on pellets, developing high-proportion pellet smelting technology, and especially developing the preparation and smelting technology of alkaline pellets have become important topics in the industry. The preparation of alkaline pellets usually involves adding limestone powder in proportion during the production process, mixing with raw materials such as iron ore powder and bentonite to form green balls. After preheating and roasting in a chain grate-rotary kiln or a belt roaster, the finished alkaline pellets are made. Using limestone powder as flux requires grinding the limestone powder to a very fine particle size to meet the requirements of pellet preparation. In addition, the decomposition and heat absorption of limestone powder during the alkaline pellet roasting process make the energy consumption of alkaline pellet production higher and the production efficiency lower than that of acidic pellets. The added limestone will also reduce the grade of the pellets.

[0006] Therefore, with the increasing energy conservation and environmental protection requirements in the steel industry, the efficient utilization of the large amount of zinc-containing dust generated by steel plants has become a major challenge. In addition, alkaline pellets help to save energy, reduce consumption and reduce emissions. How to achieve efficient production of alkaline pellets is also a difficult problem that steel companies need to solve. It is imperative to develop a new technology that can achieve both efficient utilization of zinc-containing dust and efficient preparation of alkaline pellets.

[0007] After searching, it was found that the core innovation of the present invention is that while achieving efficient recycling of zinc-containing dust, the temperature of preheating and roasting of alkaline pellets is reduced and alkaline pellets with a compressive strength greater than 3000N / P are obtained. Summary of the invention

[0008] In view of a series of difficulties in treating zinc-containing dust and producing alkaline pellets in steel enterprises, the purpose of the present invention is to provide a method for treating zinc-containing dust and producing alkaline pellets. The method can achieve efficient recovery and utilization of zinc-containing dust, and at the same time reduce the preheating and roasting temperature of alkaline pellets, which is conducive to achieving energy conservation and consumption reduction and reducing carbon emissions in steel plants.

[0009] The present invention provides the following technical solutions: 1. A method for treating zinc-containing dust and producing alkaline pellets, comprising the following steps:

[0010] (1) The zinc-containing dust and the calcifying agent are mixed in proportion, and then a binder and water are added to form agglomerates; a mixture agglomerate is obtained; in the mixture agglomerate, the molar ratio of CaO / (ZnO+Fe 2 O 3 )=2.0-3.0;

[0011] (2) calcining the mixture agglomerates obtained after agglomeration, and converting the zinc ferrite in the zinc-containing dust into zinc oxide after calcining, and the temperature of calcining is 1100-1300° C.;

[0012] (3) crushing and grinding the agglomerates obtained after roasting in step (2) and then subjecting them to ammonia leaching, using electrolysis to recover zinc from the obtained zinc-containing leaching solution, and filtering the leached residue and then drying it.

[0013] (4) The leached residue dried in step (3) is fully mixed with iron ore concentrate powder, a binder and water to prepare alkaline green pellets, and the green pellets are dried, preheated, roasted and cooled to obtain alkaline pellets; the binary alkalinity of the alkaline pellets is in the range of 0.3-1.5; the preheating temperature is 750-1020° C. and the preheating time is 3-8 min.

[0014] In the mixed material agglomerate of the present invention, the molar ratio of CaO / (ZnO+Fe 2 O 3)=2.0-3.0; This is because the addition of calcium oxide reacts with the zinc ferrite in the zinc-containing dust to generate calcium ferrite and zinc oxide, which is beneficial to the subsequent extraction of zinc. At the same time, the generated calcium ferrite helps to obtain a higher consolidation strength at a lower preheating roasting temperature during the subsequent alkaline pellet production.

[0015] In a preferred embodiment, the calcifying agent in step (1) is at least one selected from calcium-containing substances such as calcium carbonate, calcium oxide, calcium hydroxide, limestone, and slaked lime.

[0016] In a preferred embodiment, the agglomeration method in step (1) includes pelletizing and / or briquetting, and the agglomerate particle size range after agglomeration is 3-20 mm.

[0017] In a preferred embodiment, the temperature of the calcification roasting in step (2) is 1100-1250°C, preferably 1100-1220°C, and the roasting time is 1-4 hours, preferably 1-3.5 hours. The reason why the calcification roasting temperature is controlled in the present invention is that if the calcification roasting temperature is too low, it is not conducive to the preparation of high-strength alkaline pellets by low temperature and short-time preheating in the later stage. In the present invention, as one of the preferred embodiments, the calcification roasting temperature can be selected to be lower, such as 1100-1150°C, and the roasting time matched therewith is 2.5-3.5 hours.

[0018] In a preferred embodiment, the agglomerates in step (3) are crushed and ground to a particle size of ≤1 mm.

[0019] In a preferred embodiment, the ammonia immersion solution in step (3) is NH 3 ·H 2 O and NH 4 Cl / ammonium sulfate composition.

[0020] In a preferred embodiment, the binder in step (4) includes one or more of bentonite, organic binder, composite binder, etc.

[0021] In a preferred embodiment, the binary basicity of the alkaline pellets in step (4) is preferably in the range of 0.3-1.0, and more preferably in the range of 0.3-0.8.

[0022] Preferably, the drying temperature in step (4) is 200-400°C.

[0023] In a preferred embodiment, the preheating temperature in step (4) is 750-1020°C, preferably 800-1010°C, and the preheating time is 4-7 min.

[0024] In a preferred embodiment, the calcination temperature in step (4) is 1150-1250° C., preferably 1180-1250° C., and the calcination time is 6-10 min.

[0025] In industrial applications, the calcination temperature is 1100-1150°C and the calcination time is 2.5-3.5 hours; the preheating temperature in step (4) is matched to be 880-1010°C, the calcination temperature is preferably 1210-1240°C, and the time is controlled at 6-10 minutes.

[0026] The compressive strength of the alkaline pellets obtained by the present invention is greater than 3000 N / P. After optimization, it can be greater than 3400 N / P. The present invention can obtain alkaline pellets with a compressive strength greater than 3000 N / P by using a lower preheating temperature and a lower roasting temperature in the later stage.

[0027] The advantages of the present invention are that the difficult-to-use zinc ferrite resources in the zinc-containing dust are converted into zinc oxide through calcination roasting, which is easy to be extracted by subsequent ammonia leaching, has low leaching cost and good selectivity, and impurities such as calcium and silicon are not leached. The calcifying agent used is cheap and easy to obtain. Compared with pyrocarbonization reduction, it does not need to add coke or reducing coal as a reducing agent, and the reaction rate is fast, and the zinc leaching rate can reach more than 90%. When limestone is traditionally used as a flux, the decomposition of limestone requires heat absorption, resulting in high energy consumption in alkaline pellet production. The main component of the leached slag is calcium ferrite. Using it as a calcium flux for alkaline pellets can significantly reduce the preheating and roasting temperature and time, and improve production efficiency. The principle is that the calcified roasted leached slag containing zinc dust has achieved pre-slagging with calcium ferrite. Therefore, compared with the commonly used limestone flux in the pellet production process, the preheating and roasting time and the required energy consumption are significantly shortened. The present invention can realize the disposal of zinc-containing dust in the steel plant, and at the same time promotes the efficient and high-quality production of high-strength alkaline pellets, which plays an important role in achieving the goal of energy saving and consumption reduction in steel production. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a process flow chart of Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The specific embodiments of the present invention are further described below by way of examples, but the specific embodiments of the present invention are not limited to the following examples.

[0030] In the embodiments of the present invention, unless otherwise specified, the means used are all conventional means in the art, and the reagents used can be obtained through conventional commercial channels.

[0031] The technical solution of the present invention is described in detail below through specific embodiments and drawings.

[0032] Example 1

[0033] A zinc-containing dust (TZn 10.12%, ZnFe 2 O 467.12%), crush the raw ore to -1mm, add slaked lime, and control the effective CaO / (ZnO+Fe 2 O 3 The molar ratio of ) is 3.0:1, and after being fully mixed, the mixture is granulated into small balls of 3 to 20 mm. The mixture is calcified and roasted at a temperature of 1300°C for 1 hour. After cooling, it is broken into -1 mm and subjected to ammonia leaching. The ammonia leaching system is as follows: the solid-liquid ratio is 100 g / L, the leaching temperature is 60°C, the leaching time is 120 min, and the leaching liquid is ammonium sulfate-NH 3 ·H 2 O solution (ammonium sulfate and NH 3 ·H 2 O molar concentration ratio is 1:1), the total ammonia concentration in the leachate is 6 mol / L, and the zinc leaching rate is 93.38% after the leachate is filtered. The zinc is subsequently recovered by electrolysis. The leached residue is dried and mixed with iron concentrate (TFe65.23%, SiO 2 =3.75%), bentonite, water mixed and pelletized, control the basicity of pellets CaO / SiO 2 The mass ratio is 1.5, the preheating temperature is 800℃, the time is 6min, the roasting temperature is 1200℃, the time is 10min, and the alkaline pellets with a compressive strength of 3015N / P are obtained.

[0034] Example 2

[0035] A zinc-containing dust (TZn 10.12%, ZnFe 2 O 4 67.12%), crush the raw ore to -1mm, add quicklime, and control the effective CaO / (ZnO+Fe 2 O 3 ) is 2.5:1, and after being fully mixed, the mixture is granulated into small balls of 3 to 20 mm. The mixture is calcified and roasted at a temperature of 1200°C for 2 hours. After cooling, it is broken into -1 mm and subjected to ammonia leaching. The ammonia leaching system is as follows: the solid-liquid ratio is 100 g / L, the leaching temperature is 40°C, the leaching time is 180 min, and the leaching liquid is NH 4 Cl-NH 3 ·H 2 O solution (NH 4 Cl and NH 3 ·H 2 O molar concentration ratio is 1:1), the total ammonia concentration in the leachate is 6 mol / L, and the zinc leaching rate is 94.45% after filtering the leachate. The zinc is subsequently recovered by electrolysis. The leached residue is dried and mixed with iron concentrate (TFe 65.23%, SiO 2 =3.75%), bentonite, water mixed and pelletized, control the basicity of pellets CaO / SiO2 The mass ratio is 0.8, the preheating temperature is 900℃, the time is 6min, the roasting temperature is 1230℃, the time is 8min, and the alkaline pellets with a compressive strength of 3463N / P are obtained.

[0036] Example 3

[0037] A zinc-containing dust (TZn 10.12%, ZnFe 2 O 4 67.12%), crush the raw ore to -1mm, add calcium oxide, and control the effective CaO / (ZnO+Fe 2 O 3 The molar ratio of ) is 2.0:1, and after being fully mixed, the mixture is granulated into small balls of 3 to 20 mm. The mixture is calcified and roasted at a temperature of 1100°C for 3 hours. After cooling, it is broken to -1 mm and subjected to ammonia leaching. The ammonia leaching system is as follows: the solid-liquid ratio is 100 g / L, the leaching temperature is 40°C, the leaching time is 180 min, and the leaching liquid is ammonium sulfate-NH 3 ·H 2 O solution (ammonium sulfate and NH 3 ·H 2 O molar concentration ratio is 1:1), the total ammonia concentration in the leachate is 6 mol / L, and the zinc leaching rate is 92.72% after the leachate is filtered. The zinc is subsequently recovered by electrolysis. The leached residue is dried and mixed with iron concentrate (TFe65.23%, SiO 2 =3.75%), bentonite, water mixed and pelletized, control the basicity of pellets CaO / SiO 2 The mass ratio is 0.3, the preheating temperature is 1000℃, the time is 6min, the roasting temperature is 1230℃, the time is 8min, and the alkaline pellets with a compressive strength of 3568N / P are obtained.

[0038] Example 4

[0039] A zinc-containing dust (TZn 10.12%, ZnFe 2 O 4 67.12%), crush the raw ore to -1mm, add limestone, and control the effective CaO / (ZnO+Fe 2 O 3 ) is 2.0:1, and after being fully mixed, the mixture is granulated into small balls of 3 to 20 mm. The mixture is calcined at a temperature of 1220°C for 1.5 hours, and then broken into -1 mm after cooling. The ammonia leaching system is as follows: the solid-liquid ratio is 100 g / L, the leaching temperature is 40°C, the leaching time is 180 min, and the leaching liquid is NH 4 Cl-NH 3 ·H 2 O solution (NH4 Cl and NH 3 ·H 2 O molar concentration ratio is 1:1), the total ammonia concentration in the leachate is 6 mol / L, and the zinc leaching rate is about 92% after the leachate is filtered. The zinc is subsequently recovered by electrolysis. The leached residue is dried and mixed with iron concentrate (TFe65.23%, SiO 2 =3.75%), bentonite, water mixed and pelletized, control the basicity of pellets CaO / SiO 2 The mass ratio is 1.0, the preheating temperature is 1000℃, the time is 6min, and the roasting temperature is 1200℃, the time is 6min, and the alkaline pellets with a compressive strength of 3405N / P are obtained.

[0040] Comparative Example 1

[0041] Iron concentrate (TFe 65.23%, SiO 2 =3.75%), limestone, bentonite, water are mixed and pelletized to control the basicity of the pellets CaO / SiO 2 The mass ratio is 0.8, the preheating temperature is 1050℃, the time is 15min, the roasting temperature is 1250℃, the time is 10min, and the alkaline pellets with a compressive strength of 2418N / P are obtained.

[0042] Comparative Example 2

[0043] Iron concentrate (TFe 65.23%, SiO 2 =3.75%), limestone, bentonite, water are mixed and pelletized to control the basicity of the pellets CaO / SiO 2 The mass ratio is 1.5, the preheating temperature is 1100°C, the time is 20 minutes, the roasting temperature is 1250°C, and the time is 20 minutes, and the alkaline pellets with a compressive strength of 2765N / P are obtained.

[0044] By comparison, it can be found that compared with the conventional scheme, the scheme proposed in the present invention can reduce the preheating temperature of the alkaline pellets by more than 100°C, and the time is significantly shortened, which is beneficial to the efficient production organization of the alkaline pellets. At the same time, the compressive strength of the obtained alkaline pellet ore is significantly higher.

[0045] Comparative Example 3

[0046] Other conditions are the same as those in Example 1, except that:

[0047] A zinc-containing dust (TZn 10.12%, ZnFe 2 O 467.12%), crush the raw ore to -1mm, add slaked lime, control the effective CaO / (ZnO) molar ratio to 1.0:1, mix thoroughly and granulate into small balls of 3-20mm, calcify and roast the mixture at a temperature of 950℃ for 2 hours,

[0048] After drying, the leached residue was mixed with iron concentrate (TFe 65.23%, SiO 2 =3.75%), bentonite, water mixed and pelletized, control the basicity of pellets CaO / SiO 2 The mass ratio is 1.5, the preheating temperature is 800℃, the time is 6min, the roasting temperature is 1200℃, the time is 10min, and the alkaline pellets with a compressive strength of 2015N / P are obtained.

[0049] Comparative Example 4

[0050] Other conditions are the same as those in Example 1, except that:

[0051] A zinc-containing dust (TZn 10.12%, ZnFe 2 O 4 67.12%), crush the raw ore to -1mm, add slaked lime, and control the effective CaO / (ZnO+Fe 2 O 3 ) in a molar ratio of 1:2, and after being fully mixed, the mixture is granulated into small balls of 3 to 20 mm, and the mixture is calcined at a temperature of 1300°C for 1 hour.

[0052] After drying, the leached residue was mixed with iron concentrate (TFe 65.23%, SiO 2 =3.75%), bentonite, water mixed and pelletized, control the basicity of pellets CaO / SiO 2 The mass ratio is 1.5, the preheating temperature is 800℃, the time is 6min, the roasting temperature is 1200℃, the time is 10min, and the alkaline pellets with a compressive strength of 2356N / P are obtained.

[0053] Comparative Example 5

[0054] The other conditions were the same as those in Example 1, except that the leached slag was mixed with iron concentrate (TFe 65.23%, SiO 2 =3.75%), bentonite, water mixed and pelletized, control the basicity of pellets CaO / SiO 2 The mass ratio is 2, the preheating temperature is 800℃, the time is 6min, the roasting temperature is 1200℃, the time is 10min, and the alkaline pellet with a compressive strength of 2678N / P is obtained.

[0055] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. For those skilled in the art, improvements and changes obtained without departing from the technical concept of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for treating zinc-containing dust and producing alkaline pellets, characterized in that: The following steps are involved: (1) fully mixing zinc-containing dust and a calcifying agent in proportion, adding a binder and water to form agglomerates; obtaining mixed material agglomerates; in the mixed material agglomerates, the molar ratio of CaO / (ZnO+Fe2O3)=2.0-3.0; (2) calcining the mixture agglomerates obtained after agglomeration, and converting the zinc ferrite in the zinc-containing dust into zinc oxide after calcining, and the temperature of calcining is 1100-1300° C.; (3) crushing and grinding the agglomerates obtained after roasting in step (2) and then subjecting them to ammonia leaching, using electrolysis to recover zinc from the obtained zinc-containing leaching solution, and filtering the leached residue and then drying it. (4) The leached residue dried in step (3) is fully mixed with iron ore concentrate powder, a binder and water to prepare alkaline green pellets, and the green pellets are dried, preheated, roasted and cooled to obtain alkaline pellets; the binary alkalinity of the alkaline pellets is in the range of 0.3-1.5; the preheating temperature is 750-1020° C. and the preheating time is 3-8 min.

2. A method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The calcifying agent in step (1) is at least one selected from calcium-containing substances such as calcium carbonate, calcium oxide, calcium hydroxide, and limestone.

3. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The agglomeration method in step (1) includes methods such as balling or agglomeration, and the agglomerate particle size range after agglomeration is 3-20 mm.

4. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The temperature of the calcification calcination in step (2) is 1100-1250° C., preferably 1180-1220° C., and the calcination time is 1-3 hours, preferably 2-3 hours.

5. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The agglomerates described in step (3) are crushed and ground to a particle size of ≤1 mm.

6. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The ammonia immersion solution in step (3) consists of NH3·H2O and NH4Cl / ammonium sulfate.

7. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The binder in step (4) includes one or more of bentonite, organic binder, composite binder, etc.

8. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The binary basicity range of the alkaline pellets in step (4) is preferably 0.3-1.

0.

9. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The preheating temperature in step (4) is 750-1020°C, preferably 800-1010°C, and the preheating time is 4-7 minutes; the calcination temperature in step (4) is 1180-1250°C.

10. The method for treating zinc-containing dust and producing alkaline pellets according to claim 1, characterized in that: The compressive strength of the obtained alkaline pellets is greater than 3000N / P. After optimization, it can be greater than 3400N / P.